Mediator-based electron transfer pathways in microorganisms - Gemünde, André; Justus Liebig University Giessen (My University, 2024)
Challenges in industrial biotechnology arise, among other things, when dissolved O2 is required as an electron acceptor in aqueous fermentation media. These challenges mainly consist of the low solubility of the gas at cultivation temperatures, increased foaming, and the risk of explosion when combined with H2 as a substrate. Electrodes could replace O2 as electron acceptors, thereby enabling gas fermentation with Cupriavidus necator, a β-proteobacterium used for the production of basic chemicals from H2/CO2 mixtures. Although electron transfer between microorganisms and electrodes has already been demonstrated using soluble mediators, knowledge of their precise interaction is still lacking to fully replace O2. The aim of this dissertation was to develop screening and reactor systems and to identify key components in the metabolism of C. necator influencing the extracellular electron transfer. To this end, a 300 mL bioelectrochemical reactor was designed and initially characterized with Vibrio natriegens. The mediator-based and direct electron transfer of the organism was demonstrated, showing a measurable impact on product and biomass yield. As a measure of the efficiency of the artificial mediated electron transfer process, the percentage of O2 replaced by anodic electron transfer was introduced. Furthermore, a 3.5 mL screening system was developed that enables online measurement of cell density and the redox state of the mediators. Pseudomonas putida was used for verification, as its ferricyanide mediated electron transfer is already described in the literature. The screening of 14 mediators with variable redox potentials in combination with C. necator in the developed system revealed a potential window for mediator reduction, along with a current production of -365 to 206 mV vs. Ag/AgCl, with ferricyanide proving most efficient with a total of 8.4 reduction and oxidation cycles (turnovers). The established 300 mL reactors were then used for the electrochemical cultivation of C. necator to elucidate the electron transfer. Cytochrome c reductase, cytochrome c oxidase, and nitrate/nitrite reductase were identified as key complexes in ferricyanide reduction through RT-qPCR, specific inhibition, and deletion mutants. This work lays the foundation for screening mediators with microorganisms that are validated in larger reactors and also provides a basis for optimizing ferricyanide-mediated electron transfer in C. necator and other organisms.
Mediatorbasierte Elektronentransferwege in Mikroorganismen
Keywords: Redoxmediatoren; Bioelektrochemie; Elektronentransfer; Biokatalyse; Anodenatmung; ddc:620